Perspectives On The Philosophy Of Education Progressivism In Learning Models Ubiquitous Learning - Remerta N. Naatonis; Siti Masitoh; Mochamad Nursalim (FALASIFA : Jurnal Studi Keislaman, 2022)
The development of technology in the world of education gave birth to various new learning models and methods, one of which is Ubiquitous Learning. Ubiquitous Learning is u-u-learning, referred to as u-learning, leveraging digital content, physical environments, mobile devices, pervasive components, and wireless communication to provide users with a teaching-learning experience anytime, anywhere, and anywhere. The birth of Ubiquitous Learning is in line with and in line with the philosophical view of progressivism which considers education to always innovate or change in accordance with the changing times and science and technology in another sense the philosophy of progressivism is a school of modern educational philosophy that wants a change in the implementation of education to be more advanced. This study aims to analyze uLearning learning in the perspective of the philosophy of progressivism to see the relationship and assess the compatibility of the two concepts in indonesian education today, the research method uses qualitative methods with a literature review approach on Ubiquitous Learning and analyzed using the philosophical theory of progressivism. The results of the study can be explained as follows, first: Ubiquitous Learning is a learning model in which there is a separation between students and teachers in the teaching and learning process so that students are emphasized to learn more independently from where and at any time by using technological facilities and networks both the philosophy of progressivism education is a belief in the natural power of man, the power that is passed on to humans from birth who have been bring basic talents and abilities or potentials, especially their resourcefulness, so that humans will be able to overcome all the problems of their lives Third: the philosophy of progressivism education views the elements contained in distance education model Ubiquitous Learning as an effort to provide alternative education that is constrained to follow education in general.